2015
DOI: 10.1152/ajpheart.00278.2014
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of angiopoietin like-2 protects against angiotensin II-induced cerebral endothelial dysfunction in mice

Abstract: ) is a circulating pro-inflammatory and pro-oxidative protein, but its role in regulating cerebral endothelial function remains unknown. We hypothesized that in mice knockdown (KD) of angptl2, cerebral endothelial function would be protected against ANG II-induced damage. Subcutaneous infusion of ANG II (200 ng·kg Ϫ1 ·min Ϫ1 , n ϭ 15) or saline (n ϭ 15) was performed in 20-wk-old angptl2 KD mice and wild-type (WT) littermates for 14 days. In saline-treated KD and WT mice, the amplitude and the sensitivity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…To confirm these results, we measured the fluorescence associated with NO (DAF-2) and H 2 O 2 (DCFDA) release in isolated arteries 36,37 during FMD induced by a shear stress of 20 dyn/cm 2 , in both SP and PP conditions. In all conditions, fluorescence was extinguished by L-NNA confirming the unique involvement of eNOS in FMD ( Figure 3).…”
Section: Impact Of Pulsatile Pressure On Myogenic Tonementioning
confidence: 86%
See 1 more Smart Citation
“…To confirm these results, we measured the fluorescence associated with NO (DAF-2) and H 2 O 2 (DCFDA) release in isolated arteries 36,37 during FMD induced by a shear stress of 20 dyn/cm 2 , in both SP and PP conditions. In all conditions, fluorescence was extinguished by L-NNA confirming the unique involvement of eNOS in FMD ( Figure 3).…”
Section: Impact Of Pulsatile Pressure On Myogenic Tonementioning
confidence: 86%
“…27,36,37 Arterial segments were incubated with or without L-NNA (100 lmol/L) or PEGcatalase (100 U/mL) for 30 min, washed three times with PSS, pre-constricted with phenylephrine and then exposed to a shear stress of 20 dyn/cm 2 ; during the dilation, NO-or H 2 O 2 -fluorescence was quantified.…”
Section: Fluorescence Studiesmentioning
confidence: 99%
“…Several studies have correlated the levels of angiopoietin-1 and -2 with cerebral malaria severity and survival (37,(39)(40)(41). Interestingly, a relation between AT1/AT2 activity and angiopoietin-2 levels has been described in endothelial cells (42,43), possibly mediated by VEGF (44,45), that may link the activities of both pathways in vivo.…”
Section: Immortalization and Culture Of Hbmecs And Other Endothelial mentioning
confidence: 99%
“…Little is known about the impact of angptl2 on endothelial function and vice versa . We, and others, reported that recombinant angptl2 significantly reduced acetylcholine-induced dilation of isolated mouse arteries and, conversely, that angptl2 knockdown or knockout mice were protected against endothelial dysfunction induced by a high-fat diet [ 18 , 27 ] and chronic infusion of low dose angiotensin II [ 41 ]. Altogether, these data suggest that angptl2 could be a marker of endothelial function.…”
Section: Discussionmentioning
confidence: 99%